The luck of the fall - Daniels, Jim 1956- (Michigan State University Press, 2023)
"These short stories take place along Eight Mile Road on the edge of Detroit; the characters in them take consolation in their lack of prizes, in the clarity of their failures, while approaching the future with gallows humor and jaded naivety"--
Keywords: short stories; Short stories; Nouvelles